Penerapan Prinsip Good Governance dalam Pengelolaan Dana Desa Menurut Perspektif Islam (Studi Kasus Pada Desa Sungai Langka Kec Gedong Tataan Kab Pesawaran) - Rosydalina Putri; Nadia Cahya Oktavia (Jurnal Akuntansi dan Audit Syariah)
With the high potential for cases and losses that occur in the village fund program, it raises demands from the community and the government itself to the village apparatus in carrying out village fund management activities in accordance with good governance. The purpose of this study is to determine the transparency and accountability of planning, implementation, accountability, and supervision of ADD financial management in Gedong Tataan District, Pesawaran Regency in achieving good governance. This research is qualitative research. Research that produces descriptive data in the form of written or spoken words of people and observable behavior. The results of this study show that the application of transparency and accountability in The management of village funds in Sungai Langka Village has been successful in accordance with the established principles and rules and has been quite good by involving the village community in planning the allocation of village funds, as well as the responsibility in managing village funds in accordance with Permendagri regulation 113 of 2014. Supervision of ADD financial management carried out by DPMD as a supervisor serves to determine village regulations together with the village head who has carried out his duties properly. The implementation of good governance from an Islamic perspective has been applied quite well, this is based on paying attention to the verses of the Qur'an and the Sunnah of the Prophet SAW can be found some basic values that can be translated into the principles of good governance.